2013
DOI: 10.3176/earth.2013.15
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Silurian vertebrate biozones and their correlation with the conodont succession

Abstract: The first vertebrate-based subdivisions of Silurian strata were mainly drawn on material from outcrops in Britain and drill cores from the southern Baltic. Nearly twenty years ago the first vertebrate biozonal scheme was developed on the basis of vertebrate distribution in several continuous drill core sections in the northern Baltic. This paper presents a new scheme in which many new data on vertebrate distribution from the Baltica (Baltic region, NW Russia), Avalonia (southern Britain, eastern Canada), Laure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(76 citation statements)
references
References 40 publications
6
68
0
Order By: Relevance
“…Oz. bohemica ranges into the lower Gorstian in Britain and elsewhere (Aldridge & Schönlaub ; Viira & Aldridge ; Märss & Männik ) and this range served as a base for the corresponding O. bohemica bohemica Biozone sensu lato , distinguished by Aldridge & Schönlaub (). No better resolved zonations for the middle Silurian in the Midland Platform have been proposed since, therefore the entire interval with Oz.…”
Section: Resultsmentioning
confidence: 99%
“…Oz. bohemica ranges into the lower Gorstian in Britain and elsewhere (Aldridge & Schönlaub ; Viira & Aldridge ; Märss & Männik ) and this range served as a base for the corresponding O. bohemica bohemica Biozone sensu lato , distinguished by Aldridge & Schönlaub (). No better resolved zonations for the middle Silurian in the Midland Platform have been proposed since, therefore the entire interval with Oz.…”
Section: Resultsmentioning
confidence: 99%
“…falls within the C. murchisoni Zone, i.e. below the Wenlock/Ludlow boundary (Jeppsson et al, 2006;Märss and Männik, 2013). Samtleben et al (2000) identified elevated δ 13 C carb values (up to 2.28‰) in the Klinteberg Fm.…”
Section: Geological Settingmentioning
confidence: 97%
“…martinssoni allows assigning the entire studied interval to the Par. martinssoni vertebrate Zone (Karatajūtė-Talimaa, 1978; Märss and Männik, 2013) and Kockelella ortus absidata conodont Zone sensu Melchin et al (2012).…”
Section: Vertebratesmentioning
confidence: 97%
See 1 more Smart Citation
“…With the exception of the East Baltic (e.g. Märss & Männik 2013), the conodont zonation of the Homerian Stage based on Gotland has not yet been tested in other regions. Two zones, Ozarkodina bohemica longa and Kockelella ortus absidata, were, however, incorporated to the generalized global conodont zonal scale by Cramer et al (2011).…”
Section: Introductionmentioning
confidence: 97%